Legal Protection for Street Children in Connection With State Responsibility from the Pancasila Perspective - Sahat Maruli Tua Situmeang; Musa Darwin Pane; Subagyo Sri Utomo; Diah Pudjiastuti (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to determine the legal protection of street children associated with state responsibility and to find out what efforts should be made by the government in dealing with the phenomenon of street children in order to realize social welfare in the perspective of Pancasila. The approach method in this research is a normative juridical approach. The specification of the research used descriptive analytical method. The results of this study conclude that the laws and regulations currently used to eradicate and overcome the rampant street children are not sufficient, namely the occurrence of a legal vacuum, especially in parenting patterns in their biological families, where the failure of parenting is manifested by violence experienced by children, both violence and violence. physically and psychologically as well as prevention of child marriage which results in victims. The efforts made by the government in alleviating and tackling street children are the establishment of a child social welfare program (PKSA), a child social welfare institution (LKSA), a child protection task force (Satgas PA), where these efforts are felt to be not optimal. Based on this, the authors are of the view that in order to realize social welfare in the perspective of Pancasila is through institutional strengthening of the Social Service and Child Protection Commission, as well as institutional strengthening both through government administration and non-government administration, such as strengthening the functions of the Rukun Tetangga and Rukun Warga as well as coaching the community in an effort to prevention of the phenomenon of street children as well as strengthening regulations, namely reformulation and reconstruction of policies reformulation of laws and regulations relating to child protection.